Environmental sustainability and the impact of pollution on urban space in Sétif: Eulma City as a model - Bennani, Nardjes (Journal of Architecture and environment of child, 2022)
Today, the environment suffers from several problems, the most important of which is pollution. This problem has become the major concern of all countries in the world as it is considered one of the greatest threats to the environment. Attention to the environment and its problems is still lagging behind in developing countries. Although Algeria is one of these countries, it has made great progress in the field of environmental protection. Today, it is striving to restore respect for the environment in general and the urban environment in particular, which is in a degraded state. Several factors have contributed to the emergence of this situation, particularly in large cities. This paper addresses the issue of environmental pollution in the wilaya of Setif and takes as a case study the city of El-Eulma, which is characterised by its urban-industrial character, the rapid growth of its population and the changes that its community is experiencing. All this has contributed to the emergence of many environmental problems such as the increasing number of pollution sources and the components of living and non-living resources that are damaged by toxins from fumes, gases, toxic compounds, waste, noise, etc. The problems of environmental degradation and pollution are more related to urban areas than to other regions of the wilaya of Setif. This is mainly due to the absence of a rational urban planning policy and the poor distribution of development projects throughout the country's wilayas. The city of El Eulma has become a focus of several types of pollution that have affected its entire region. The importance of the study lies in the knowledge of the reality and the extent of the impact of the pollution phenomenon on the urban area of the wilaya of Setif and more particularly in the city of El Eulma, as it is one of the problems present in the wilaya. To develop this study, we opt for a field survey through which we interview the community and local authorities. Then, we analyse the factors that have caused this phenomenon while looking for the dominant forms of pollution in the city and how they affect the urban area. Finally, we propose some solutions to reduce this phenomenon.